2002
DOI: 10.1063/1.1447532
|View full text |Cite
|
Sign up to set email alerts
|

Exchange anisotropy between single twin domain NiO and NiFe

Abstract: Single-twin (T)-domain NiO films were obtained by stress induced during the growth, and the exchange anisotropy between NiO and NiFe films was studied by using micromagnetic modeling. The compressive strain along the [111] is −7.16×10−4, which forces spins of NiO to lie on the (111) plane parallel to the film surface. The neutron diffraction shows that the moments of NiO predominantly lie in the film plane with random orientations, that is, the NiO is of a single T-domain, and multi-spin-rotation-domains in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The maximum excursion registered in the 1×1 µm 2 AFM image, reported in figure 8(b), is only 6.4 nm, corresponding to 5-6 NBCO uc. The islands are not so defined as those reported by other groups for NBCO pulsed laser deposited films using a stoichiometric target [33,34]. The height of the island steps is about 1 NBCO uc.…”
Section: Afm Analysismentioning
confidence: 81%
“…The maximum excursion registered in the 1×1 µm 2 AFM image, reported in figure 8(b), is only 6.4 nm, corresponding to 5-6 NBCO uc. The islands are not so defined as those reported by other groups for NBCO pulsed laser deposited films using a stoichiometric target [33,34]. The height of the island steps is about 1 NBCO uc.…”
Section: Afm Analysismentioning
confidence: 81%
“…Indeed, Kurosawa et al 54 reported an extremely low value for well-annealed single crystals of only 29.5 J m −3 . Our experimental situation, however, may be more compatible with a layer coupled to a single crystal as, e.g., reported by Lai et al 4 for NiO͑111͒/ NiFe. In this case, a considerably higher value of 1360 J m −3 was found for the NiO anisotropy within the ͑111͒ plane, which might be more realistic due to the interaction with the coupled layer.…”
Section: B Magnetoelastic Couplingmentioning
confidence: 75%